2012
DOI: 10.1021/ja211576b
|View full text |Cite
|
Sign up to set email alerts
|

Heme Flattening Is Sufficient for Signal Transduction in the H-NOX Family

Abstract: The H-NOX family of nitric oxide (NO) sensing proteins has received considerable attention because its members include the mammalian NO sensor, soluble guanylate cyclase. Despite this attention, the mechanism of signal transduction has not been elucidated. Structural studies of bacterial members of the family have revealed that the H-NOX heme cofactor is extremely distorted from planarity. Furthermore, it has been determined that heme distortion is maintained primarily by a conserved proline residue located in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…Since there was no direct evidence in support of this hypothesis, however, our lab investigated the role of the H-NOX haem structure in the H-NOX/HaCE signalling pathway from S. woodyi . In this study, as expected, the relaxed haem proline mutant of Sw -H-NOX led to upregulation of the phospho-diesterase activity of Sw -HaCE (Muralidharan & Boon, 2012), which is the very same effect that NO-bound H-NOX has on HaCE activity (Liu et al, 2012). This study, therefore, provided the first direct evidence for the role of haem relaxation in H-NOX signal transduction.…”
Section: Biochemical Functions Of H-nox Proteinssupporting
confidence: 85%
See 1 more Smart Citation
“…Since there was no direct evidence in support of this hypothesis, however, our lab investigated the role of the H-NOX haem structure in the H-NOX/HaCE signalling pathway from S. woodyi . In this study, as expected, the relaxed haem proline mutant of Sw -H-NOX led to upregulation of the phospho-diesterase activity of Sw -HaCE (Muralidharan & Boon, 2012), which is the very same effect that NO-bound H-NOX has on HaCE activity (Liu et al, 2012). This study, therefore, provided the first direct evidence for the role of haem relaxation in H-NOX signal transduction.…”
Section: Biochemical Functions Of H-nox Proteinssupporting
confidence: 85%
“…Based on homology to sGC and genomic association with signalling proteins, it was hypothesized that bacterial H-NOX proteins would also serve as sensors of NO (or possibly O 2 in the case of obligate aerobic organisms), regulating signal transduction of the associated signalling proteins. Many subsequent studies have confirmed the role of the interaction of H-NOX with NO in modulating the activities of these proteins (Arora & Boon, 2012; Henares, Higgins, & Boon, 2012; Henares, Xu, & Boon, 2013; Liu et al, 2012; Muralidharan & Boon, 2012); these studies will be described later in this review (see Section 6).…”
Section: Discovery Of a Bacterial No Sensing Protein: H-noxmentioning
confidence: 87%
“…I5) are responsible for translating the heme relaxation to an upward shift and rotational displacement of the entire N-terminal subdomain with respect to α-helix F. Functional validation of the heme strain model has been attained by testing the influence of H-NOX heme conformation on the enzyme activity of its effector protein. The P117A mutation in the H-NOX of Shewanella woodyi , which leads to a planar heme, is sufficient to mimic the NO-activated H-NOX state [51]. …”
Section: Heme-nitric Oxide/oxygen Binding Proteinsmentioning
confidence: 99%
“…244,245 and in particular, for the highly non-planar conformation imposed by the protein on its single heme-cofactor. 246,247,248,249,250,251,252 This is one of the most distorted heme-cofactors to be observed in natural systems, 247 and this feature has been linked to its uncommonly high midpoint potential 248 and is likely crucial to its biological function. H-NOX proteins are proving to be particularly fruitful model systems that are being well explored.…”
mentioning
confidence: 99%
“…Other important developments include recent conformation of the connection between heme flattening and signal transduction in further mutational studies, 252 and an early technological application that involved the replacement of a single tyrosine residue to affect loss of the heme's oxygen binding ability for the creation of a NO sensor. Clearly, H-NOX provides an excellent system for understanding how and why nature exploits conformational control but it is also becoming a prototype complex for the artificial exploitation of the effect to fine-tune physicochemical properties and to go beyond.…”
mentioning
confidence: 99%